Impact of Adjuvant Radiotherapy for Malignant Salivary Gland Tumors. (4th July 2017) - Safdieh, Joseph; Givi, Babak; Osborn, Virginia; Lederman, Ariel; Schwartz, David; Schreiber, David
Abstract : Objective: Using the National Cancer Database (NCDB), we investigated the characteristics, outcomes, and benefits of adjuvant therapy for patients diagnosed with malignant salivary gland tumors between 2004 and 2012. Study Design: Retrospective analysis. Setting: NCDB. Subject and Methods: The cases of patients diagnosed with a nonmetastatic major salivary gland tumor who underwent resection between 2004 and 2012 were abstracted from the NCDB. Patients were further included if they had pT1‐4NX‐1M0 high‐grade disease or pT3‐4NX‐0M0 or pT1‐4N1M0 low‐grade disease. Patients were identified as having no postoperative radiation therapy or having received postoperative radiation therapy to a dose of 5000 and 7000 cGy to the head and neck region or the parotid region, and their characteristics and outcomes were compared. Results: During the study period, 4068 patients met the inclusion criteria for this analysis, of which 2728 (67.1%) received postoperative radiation and 1340 (32.9%) did not. With a median follow‐up of 49.1 months, there was a significant improvement in overall survival associated with those receiving postoperative radiation (5 years, 56% vs 50.6%). On multivariable analysis, radiation utilization (hazard ratio, 0.78; 95% CI, 0.71‐0.86; P < 0.001) and female sex (hazard ratio, 0.88) were associated with improved survival. When the analysis was limited to patients ≤65 years old, the survival benefit was persistent on multivariable analysis. Conclusion: In conclusion, in this large NCDB study of 4068 patients with locally advanced malignant salivary gland carcinoma, administering adjuvant radiotherapy was associated with improved overall survival.